The impact of CEO political ideology on labor cost reductions and payout decisions during the COVID-19 pandemic - Bayat, Ali; Goergen, Marc; Koutroumpis, Panagiotis; Wei, Xingjie (Journal of Corporate Finance, 2025)
Using a hand-collected dataset, we study whether CEO political ideology affected S&P 500 firms’ reactions to the COVID-19 pandemic in 2020. During the pandemic, CEOs had the option to distribute the pain of the pandemic’s impact onto shareholders by paying lower dividends, onto the workforce by reducing labor costs, or to share the pain. We hypothesize that conservative CEOs were more likely to aggressively reduce labor costs while still meeting dividend expectations. Conversely, other CEOs would have been less likely to meet dividend expectations and less likely to reduce labor costs. Our findings support this hypothesis. We also find that during the pandemic, conservative CEOs used temporary downsizing to avoid earnings losses, enabling them to meet dividend expectations.